Noise and vibration control - Munjal, M. L (Hackensack, N.J. : IISc Press : World Scientific, 2013)
Annotation Vibration and noise are two interrelated terms in the field of mechanical engineering. Vibration is caused by unbalanced inertial forces and moments whereas noise is the result of such vibrations. Noisy machines have always been a matter of concern. It is now well understood that a quieter machine is in every way a better machine. Lesser vibration ensures manufacturing to closer tolerances, lesser wear and tear, and longer fatigue life. Hence, a quieter machine is more cost-effective in the long run. This book deals with such industrial and automotive noise and vibration, their measurement and control.
Ch. 1. Noise and its measurement. 1.1. Plane wave propagation. 1.2. Spherical wave propagation. 1.3. Decibel level. 1.4. Frequency analysis. 1.5. Weighted sound pressure level. 1.6. Logarithmic addition, subtraction and averaging. 1.7. Directivity. 1.8. Measurement of sound pressure level. 1.9. Loudness. 1.10. Noise limits in India. 1.11. Masking. 1.12. Sound level meter. 1.13. Microphones. 1.14. Microphone sensitivity. 1.15. Intensity meter -- t t
engineering bookfair2015
Includes bibliographical references and index.
Keywords: Noise; Vibration; Noise control; Electronic books